Pengaruh Desain Interior, Kualitas Produk, Harga terhadap Keputusan Pembelian di Kopi Boemi Batam - Rania Zahra Aziz Nasution; Sabri Sabri; Syarifuddin Syarifuddin (Student Scientific Creativity Journal, 2026)
This research explores the factors influencing consumer purchasing decisions at Kopi Boemi Batam, focusing on interior design, product quality, and pricing policy. The primary objective is to examine the impact of these three variables on purchasing behavior, both individually and collectively. A quantitative approach was employed, with primary data collected through a Likert-scale questionnaire distributed to 99 customers selected via accidental sampling. Data were analyzed using multiple linear regression. Partial hypothesis testing T-test revealed that interior design and pricing have a positive and significant effect on purchasing decisions. Product quality demonstrated a positive trend but did not reach statistical significance. Simultaneous testing F-test confirmed that the three variables collectively exert a significant influence on purchasing decisions, accounting for 81% of the total contribution. These findings are expected to enrich the literature on marketing management, particularly within the culinary industry. Coffee shop operators are encouraged to prioritize innovative spatial design and competitive pricing strategies as key drivers of customer loyalty. Future research may consider incorporating additional variables such as service quality or digital marketing to provide a more comprehensive understanding of purchasing behavior in the coffee shop sector.